2012
DOI: 10.1179/1476830512y.0000000004
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic effects of exogenous saccharides: A review of controlled human, animal, andin vitrostudies

Abstract: ObjectivesCurrent research efforts are centered on delineating the novel health benefits of naturally derived saccharides, including growing interest in their abilities to influence neurologic health. We performed a comprehensive review of the literature to consolidate all controlled studies assessing various roles of exogenous saccharide compounds and polysaccharide-rich extracts from plants, fungi, and other natural sources on brain function, with a significant focus on benefits derived from oral intake.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 62 publications
1
24
0
1
Order By: Relevance
“…Glucan affects virtually all facets of both cellular and humoral immunity [1,2,3,8,10,32,33] . Together, with other authors Ostrasrahimi et al [33] , we conclude that glucan is beneficial in complementary and adjuvant therapy of cancer, increases quality of life, and reduces both psychical and pathophysiological impacts of anticancer treatment [26,33] . Glucan supplementation can influence the levels of IgG, interferon gamma and other hematological parameters [34] .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Glucan affects virtually all facets of both cellular and humoral immunity [1,2,3,8,10,32,33] . Together, with other authors Ostrasrahimi et al [33] , we conclude that glucan is beneficial in complementary and adjuvant therapy of cancer, increases quality of life, and reduces both psychical and pathophysiological impacts of anticancer treatment [26,33] . Glucan supplementation can influence the levels of IgG, interferon gamma and other hematological parameters [34] .…”
Section: Discussionmentioning
confidence: 96%
“…Numerous studies, with respect of our current study, evaluated the neurological effects of exogenous polysaccharides. These studies showed that many plantbased polysaccharides have positive effects on cognitive functions in both healthy population and in cancer patients [26] . In our study, we observed that supplementation with glucan caused some effects on cognitive functions and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Nelson ED. group exhibited Aloe Vera gel shows positive effects on cognitive function and mood in healthy adults and promises, when take orally, in supporting neurologic health and function [5] . In an early our in vitro study, the fermentation production of hydrophobic butyric acid was confirmed by endophytic bacteria within Aloe Vera gel, supporting the possible incorporation of Aloe Vera gel as prebiotics aimed at improving gastrointestinal health [6] .…”
Section: Possible Prophylaxes Of Aloe Vera Gel Ingestion To Butyrate mentioning
confidence: 99%
“…α and ß-glucans enhance hippocampal synaptic plasticity [46]. The sulfated polysaccharide from the brown algae Laminaria japonica, sulfated polymannuroguluronate has been reported to exhibit neuroprotective effect by decreasing apoptosis in PC12 neuronal cells, in vitro [47].…”
Section: Marine Carbohydrate Based Drugs For Ndmentioning
confidence: 99%